The THE INFLUENCE OF HOTEL MARKETING MIX ON TOURISTS’ REVISIT INTENTION Case Study at Kumala Pantai Hotel, Seminyak, Bali - Dr. Ni Luh Putu Indiani, S.E., M.M.; Ni Nyoman Rusmiati; Indra Kusuma Jaya (Fakultas Ekonomi Universitas Warmadewa, 2020)
Growth in the number of hotel rooms in Bali shows an increasing trend every year. Thus, hotel room number is far higher than the number of tourists visiting Bali. This triggered intense competition in the hotel industry especially in areas with the highest room number growth which are Sanur and Seminyak. Amidst fierce competition, the right marketing program becomes a superior strategy to ensure firm’s viability. This study aims to examine the relationship between marketing strategy in this case marketing mix strategy and tourists’ revisit intention, by conducting a case study in one of the hotels in Seminyak, Kumala Pantai Hotel. Data collection method was a survey method using a questionnaire. Multiple linear regression analysis technique was used to test the effect of independent variables on dependent variable. The results showed that marketing mix consisting of product quality, price, promotion, and location significantly drives tourists’ intention to revisit Kumala Pantai Hotel. Aspects that need to be considered to improve product quality are unique hotel designs, providing necessary and superior quality facilities. In price aspect, hotel management needs to guarantee price affordability, price compatibility with service quality and target segment. In promotion aspect, hotel management needs to design attractive advertisements and be published in the mass media, provide price incentive, and send attractive promotional content to customers’ email. In location aspect, accessibility and the surrounding area play an important role in encouraging tourists’ interest to revisit the hotel. Keywords: product quality, price, promotion, place, marketing mix, repurchase intention, revisit intention.